Occurrence of Choline and Glycine Betaine Uptake and Metabolism in the Family Rhizobiaceae and Their Roles in Osmoprotection - Boncompagni, Eric (American Society for Microbiology, 1999)
The role of glycine betaine and choline in osmoprotection of various Rhizobium, Sinorhizobium, Mesorhizobium, Agrobacterium, and Bradyrhizobium reference strains which display a large variation in salt tolerance was investigated. When externally provided, both compounds enhanced the growth of Rhizobium tropici, Sinorhizobium meliloti, Sinorhizobium fredii, Rhizobium galegae, Agrobacterium tumefaciens, Mesorhizobium loti, and Mesorhizobium huakuii, demonstrating their utilization as osmoprotectants. However, both compounds were inefficient for the most salt-sensitive strains, such as Rhizobium leguminosarum (all biovars), Agrobacterium rhizogenes, Rhizobium etli, and Bradyrhizobium japonicum. Except for B. japonicum, all strains exhibit transport activity for glycine betaine and choline. When the medium osmolarity was raised, choline uptake activity was inhibited, whereas glycine betaine uptake was either increased in R. leguminosarum and S. meliloti or, more surprisingly, reduced in R. tropici, S. fredii, and M. loti. The transport of glycine betaine was increased by growing the cells in the presence of the substrate. With the exception of B. japonicum, all strains were able to use glycine betaine and choline as sole carbon and nitrogen sources. This catabolic function, reported for only a few soil bacteria, could increase competitiveness of rhizobial species in the rhizosphere. Choline dehydrogenase and betaine-aldehyde dehydrogenase activities were present in the cells of all strains with the exception of M. huakuii and B. japonicum. The main physiological role of glycine betaine in the family Rhizobiaceae seems to be as an energy source, while its contribution to osmoprotection is restricted to certain strains.